Bringing politics back in: Towards a model of the developmental state - Leftwich, Adrian (The Journal of Development Studies, 1995)
The few cases of rapid economic growth in the Third World in the last 30 years have occurred in democratic, quasi-democratic and non-democra tic polities. They are thus clearly not a function of common regime ty pe. I suggest that they are best explained by the special character of their states, understood ‘as developmental states’. This article outl ines some common characteristics of these states. However the forms an d features of these states are not simply a function of their administ rative structures or principles of governance, but of their politics. The article thus also underlines the importance of political analysis in both development theory and policy, from where it has been extruded for too long.